India could harness public-private partnerships to achieve malaria elimination - Manju Rahi; Amit Sharma (Elsevier, 2022)
Summary: Public-private partnerships (PPP) have been beneficial in different sectors like infrastructure development and service sector across the world, including in India. Such partnerships in the healthcare sector have also been successful in providing access to affordable medical attention to all sections of society. These partnerships between public and private entities have proven to be beneficial in controlling malaria in high burden districts of India and taking these areas to the brink of elimination, thus setting examples to follow. The two successful ones are the Comprehensive Case Management Project (CCMP) in Odisha which is now adopted by the state, and the Malaria Elimination Demonstration Project (MEDP) which has nearly eliminated malaria from the highly endemic district of Mandla in Madhya Pradesh. Here we propose that non-government and semi-government actors may be given vital roles in the malaria elimination efforts till 2030 and beyond. These partners will add value to the national programme and may have the potential to develop and test different models of malaria elimination in real-life settings that the government programme can absorb sustainably.